MUSIC AS A FACTOR IN ETIOLOGY OF CRIME: CAN IT MAKE US ACCEPT THE UNACCEPTABLE? - Irfan Osmanović; Ena Kazić-Cakar (Revija za kriminologiju i krivično pravo)
With no intention to present the importance of music for our lives and for the culture, lesser than it truly has, authors are testing the role of music as a potential factor in etiology of crime. More specifically, they are trying to question whether the music lyrics whose content indicates acceptability of actions that are usually not acceptable, moreover that are criminal, might have an influence on individual so that person perpetrates criminal offence. After brief overview of criminological theories that correlate music and crime, authors will present qualitative study on lyrics of one of the most famous rap duos in Bosnia and Herzegovina, with the analysis of the text, and results of survey conducted among student population of Bosnia and Herzegovina, regarding the general and personal influence of the duo's music.